Estudio de la composición química, actividad antimicrobiana y antioxidante del aceite esencial proveniente de la corteza de la Ocotea quixos (Lam) Kosterm. - Herrera Carrión, Mónica Paulina (2017)
The present work evaluated the chemical composition and biological activity in the essential oil coming from the bark of Ocotea quixos. The oil obtained by means of distillation by steam dragging, it was analyzed by gas chromatography coupled to masses, identifying itself chemical composition. The capturing capacity of free radicals was evaluated, using the β-carotene bleaching assay the antioxidant activity was established. As natural standard, the essential oil of thyme (Thymus vulgaris) and butylhydroxyanisole (BHA) was used as a synthetic positive control. The obtained results revealed that the essential oil of Ocotea quixos presents a greater capturing capacity of free radicals with (IC50 DPPH 2.786 ± 0.150 mg/mL; IC50 ABTS 0.24017 ± 0.03357 mg/mL). The β-carotene bleaching tests determined that the antioxidant activity of the essential oil from Ocotea quixos was higher than the natural reference oil of Thymus vulgaris with IC50 of 0.4958 ± 0.0169 mg/mL. Using the method of disc diffusion the antimicrobial and antifungal activity was valued, the study was made in 12 stocks, 10 bacteria and 2 yeasts, and they were used as reference the essential oil of Thymus vulgaris and Citral. The best results of minimum inhibitory concentration (MIC) were: Staphylococcus aureus ATCC 29213 (0.11 mg/mL), Listeria grayi ATCC 19120 (0.52 mg/mL), Staphylococcus epidermidis ATCC 14990 (0.11 mg/mL), Micrococcus luteus ATCC 4698 (0.52 mg/mL), Candida albicans ATCC 10231 (0.11 mg/mL), Candida tropicalis ATCC 13803 (1. 05 mg/mL).